Effects of Different Construction Sequences on Ground Surface Settlement and Displacement of Single Long Pile due to Twin Paralleled Shield Tunneling - Kan Huang; Yiwei Sun; Xianqiang Huang; Yujian Li; Meng Jiang; Runing Liu (Advances in Civil Engineering)
Shield tunneling activities inevitably pass through pile foundations at close distance in densely urban areas. Various studies have investigated the interaction between newly constructed tunnels and existing pile foundations. However, the influence of different construction sequences of twin paralleled shield tunneling on single long pile is seldom considered. A case was found in the project of Changsha Metro Line 5, where the twin paralleled tunnels were constructed near the Wanjiali Viaduct piles. A three-dimensional finite element model was established to analyze the pier settlement, ground surface settlement trough, and the vertical and horizontal displacement of pile under different construction sequences in layered soil. The results show that the adjacent pile and surrounding environment are affected substantially with the change of construction sequence of twin paralleled tunnels. The construction sequence of condition (b), in which the tunnel closer to the pile foundation is first constructed and then the tunnel farther away from the pile foundation is second constructed, can reduce the settlement of pier by 13.1%, the maximum surface settlement by 7.0%, the maximum vertical displacement of pile foundation by 7.9%, and the maximum horizontal displacement by 6.9%. The present findings can provide reference for similar projects.